GAMBARAN KEPATUHAN PENGOBATAN MASAL DI DAERAH ENDEMIS KOTA PEKALONGAN - Marya Yenita Sitohang; Lintang Dian Saraswati; Praba Ginandjar (Jurnal Kesehatan Masyarakat (Undip), 2017)
According to WHO, filariasis is one of the tropical diseases that can be eliminated through mass drug administration (MDA). Pekalongan City has started MDA since 2011. Through an evaluation in 2016, it was known that microfilaria rate (Mf rate) remained 1%. The purpose of this study was to describe the mass drug administration compliance in filariasis endemic area of Pekalongan City. This study used a rapid survey method. A two-stages random sampling was used in this study. The first stage was selected 25 clusters randomly from 10 villages based on proportionate to population size (PPS) method using C-Survey application. The second stage was selected 10 subjects randomly from each cluster. The sample of this research was 250 people. The results showed that the compliance to MDA was 76%. The characteristics of respondents as age, sex, occupation, knowledge of filariasis POMP, perceived of severity, place of getting information and frequency of getting information significantly had no relation with compliance to MDA (p> 0,050). Recent education, knowledge of filariasis, perceived of susceptibility, perceived of benefits, perceived of barriers, internal cues to action, external cues to action, source  of MDA information and TPE support were significantly related to MDA compliance (p <0.050). Therefore, socialization that reach all levels of society was needed. Increasing the role of TPE in doing follow-up after giving the drug also needed to increase the compliance to MDA.